Adaptation of western marketing concepts for the Indonesian construction industry - Hartanto, Felix. (2008)
The purpose of this study was to form appropriate and suitable marketing concepts for the Indonesian construction industry, which are adapted from western marketing concepts but under consideration of Indonesian people and Indonesian construction industry characteristics.